The specification of documentation for anti-dumping investigation in metallurgy using ABC costing method - K. Janovská; A. Samolejová; Z. Stefanovová (Metalurgija, 2014)
In today’s globalized market economy, business companies are active both in domestic and in foreign markets, thus increasing the importance of observing the international rules providing guidelines for mutual trade among countries within the global trading system. Metallurgical materials and products are among the products in case of which anti-dumping duty is often imposed. As far as the decisions on possible dumping and its amount are concerned, the market with metallurgical products and the methodology used for calculating the dumping range have certain specific features, as stated in the article.